2014
DOI: 10.2478/s11535-014-0320-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of valerenic acid in hairy root culture of Valeriana officinalis by elicitation

Abstract: Valerenic acid (VA) is a pharmacologically-active sesquiterpene found in valerian (Valeriana officinalis L., Valerianaceae) roots and rhizomes. The plant produces only small amounts of this metabolite naturally. So, induction of hairy roots as well as elicitation can be useful to increase its commercial production. In this study, Wild-type strain ‘A13’ of Agrobacterium rhizogenes was used to induce hairy roots in valerian. The influence of three different elicitors including Fusarium graminearum extract (FE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…(2012) observed a threefold increase in valtrate content using 100 mg/L MJ treatment, in the adventitious root culture of V. amurensis. Similarly, Torkamani et al. (2014) reported increased valerenic acid production (two times higher) in V. officinalis hairy root culture with MJ (100 μM) treatment.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…(2012) observed a threefold increase in valtrate content using 100 mg/L MJ treatment, in the adventitious root culture of V. amurensis. Similarly, Torkamani et al. (2014) reported increased valerenic acid production (two times higher) in V. officinalis hairy root culture with MJ (100 μM) treatment.…”
Section: Resultsmentioning
confidence: 72%
“…Cui et al (2012) observed a threefold increase in valtrate content using 100 mg/L MJ treatment, in the adventitious root culture of V. amurensis. Similarly, Torkamani et al (2014) reported increased valerenic acid production (two times higher) in V. officinalis hairy root culture with MJ (100 mM) treatment. In the present investigation, elicitation resulted in a significant increase of VA, HVA, and AVA content, not only in the root (1.78, 7.89, and 2.38 mg/g DW) but most prominently in the leaf (2.47, 8.37 and 1.02 mg/g DW), for the first time.…”
Section: Quantification Of Valerenic Acid and Its Derivativesmentioning
confidence: 70%
See 1 more Smart Citation
“…In vitro culture of hazel ( Corylus avellana , European filbert) has been made known as a promising and inexpensive strategy for producing paclitaxel ( Gallego et al, 2017 ; Salehi et al, 2017 ; Salehi et al, 2018c ; Salehi et al, 2019b ; Salehi et al, 2019c ; Farhadi et al, 2020 ; Salehi et al, 2020 ). Biosynthesizing bioactive compounds in plants is influenced by various factors ( Torkamani et al, 2014 ; Salehi et al, 2017 ; Salehi et al, 2018a ; Salehi et al, 2018b ; Salehi et al, 2018c ; Salehi et al, 2019a ; Salehi et al, 2019b ; Salehi et al, 2019c ; Salehi et al, 2019d ). Previous studies ( Salehi et al, 2019b ; Salehi et al, 2019c ; Farhadi et al, 2020 ; Salehi et al, 2020 ) demonstrated the positive influences of cell extract (CE) and culture filtrate (CF) of endophytic fungi on paclitaxel biosynthesis in cell suspension culture (CSC) of C. avellana .…”
Section: Introductionmentioning
confidence: 99%
“…Hook. f. [44], and induction of 100 µM MeJA for 7 days promoted the production of valerian acid in valerian hairy root cultures of Valeriana o cinalis [45]. Therefore, it is necessary to screen MeJA concentration and treatment time in order to obtain the maximum accumulation of bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%